PENINGKATAN KEMAMPUAN MEMAHAMI SOAL CERITA MATEMATIKA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA SISWA KELAS VI SD - irawan, Dudun; Iis Nurasiah; Kurniasari, Efi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This Classroom Action Research (CAR) was motivated by the low ability of sixth-grade students at SD Negeri Tenjolaut to understand mathematical word problems, which was influenced by a conventional, teacher-centered learning process. The study aimed to improve students’ ability to comprehend mathematical word problems as well as enhance their learning participation through the implementation of the Problem Based Learning (PBL) model. The research was conducted from December 2025 to June 2026 and involved 23 students as participants. The study employed the Kemmis and McTaggart action research design, consisting of the stages of planning, action implementation, observation, and reflection carried out in several cycles. Data were collected through observations, tests in the form of contextual mathematical word problems, and documentation. The data were then analyzed using both qualitative and quantitative approaches.The results showed a significant improvement in both the learning process and students’ learning outcomes after the implementation of the Problem Based Learning (PBL) model. In the pre-cycle stage, the class average score was 67, with a learning mastery rate of 51% (12 students). After the implementation of PBL in Cycle I, the class average increased to 76.78, and the mastery rate reached 82.61% (19 students). Furthermore, improvements in classroom management and the provision of scaffolding in Cycle II led to even better learning outcomes, with the class average reaching 82.35 and the classical mastery rate increasing to 91.30% (21 students). In addition to the improvement in academic achievement, students’ group learning activities became more active and collaborative, while their social and spiritual attitudes also showed positive development. Therefore, it can be concluded that the implementation of the Problem Based Learning model is effective in improving students’ ability to understand mathematical word problems.